An emergency surgical airway establishment following rapid sequence induction: a rare case of laryngeal stenosis associated with tuberculosis - Ruofan Wang; Yi He; Xiaoqiang Li; Yunxia Zuo (BMC Anesthesiology)
Abstract Background Rapid sequence induction (RSI) is the standard airway management technique for patients requiring emergency surgery with a full stomach or intestinal obstruction, aiming to reduce aspiration risk. RSI may fail if an unexpected difficulty intubation occurred and then a mask ventilation had to be applied. The worst scenario is that mask ventilation also failed, severe hypoxia developed followed by cardiac arrest. Case presentation A 14-year-old child with a history of pulmonary tuberculosis diagnosed with intestinal obstruction scheduled for emergency surgery. Due to high risk of aspiration, rapid sequence induction was applied. Although the preoperative airway assessment was normal, unexpectedly difficult airway was encountered. There was a failure of vocal cord exposure under video laryngoscope. A crisis happened when mask ventilation failed. Facing the disaster of “cannot intubate, cannot ventilate” and following severe hypoxia and cardiac arrest, the anesthesiologist established a surgical airway which successfully resuscitated the patient. A rare disease of laryngeal tuberculosis might be the underlying cause. Conclusions Patients with a history of pulmonary tuberculosis should be carefully evaluated for the presence of laryngeal tuberculosis, with laryngeal imaging as an optional diagnostic component. When encountering unexpected difficult airways during rapid sequence intubation leading to hypoxic cardiac arrest, immediate surgical airway intervention is critical for patient survival.